Plant phylogeny drives arboreal caterpillar assemblages across the Holarctic. Issue 24 (7th November 2020) - Seifert, Carlo L.; Volf, Martin; Jorge, Leonardo R.; Abe, Tomokazu; Carscallen, Grace; Drozd, Pavel; Kumar, Rajesh; Lamarre, Greg P.A.; Libra, Martin; Losada, Maria E.; Miller, Scott E.; Murakami, Masashi; et al.
Abstract: Assemblages of insect herbivores are structured by plant traits such as nutrient content, secondary metabolites, physical traits, and phenology. Many of these traits are phylogenetically conserved, implying a decrease in trait similarity with increasing phylogenetic distance of the host plant taxa. Thus, a metric of phylogenetic distances and relationships can be considered a proxy for phylogenetically conserved plant traits and used to predict variation in herbivorous insect assemblages among co‐occurring plant species. Using a Holarctic dataset of exposed‐feeding and shelter‐building caterpillars, we aimed at showing how phylogenetic relationships among host plants explain compositional changes and characteristics of herbivore assemblages. Our plant–caterpillar network data derived from plot‐based samplings at three different continents included >28, 000 individual caterpillar–plant interactions. We tested whether increasing phylogenetic distance of the host plants leads to a decrease in caterpillar assemblage overlap. We further investigated to what degree phylogenetic isolation of a host tree species within the local community explains abundance, density, richness, and mean specialization of its associated caterpillar assemblage. The overlap of caterpillar assemblages decreased with increasing phylogenetic distance among the host tree species. Phylogenetic isolation of a host plant within the local plant community was correlated with lower richness and mean specialization of the associated caterpillar assemblages. Phylogenetic isolation had no effect on caterpillar abundance or density. The effects of plant phylogeny were consistent across exposed‐feeding and shelter‐building caterpillars. Our study reveals that distance metrics obtained from host plant phylogeny are useful predictors to explain compositional turnover among hosts and host‐specific variations in richness and mean specialization of associated insect herbivore assemblages in temperate broadleaf forests. As phylogenetic information of plant communities is becoming increasingly available, further large‐scale studies are needed to investigate to what degree plant phylogeny structures herbivore assemblages in other biomes and ecosystems. Abstract : Host plant phylogenetic relationships have been shown to affect community composition and interaction networks of associated insect herbivores. Using a cross‐continental dataset, we showed that phylogenetically isolated hosts harbored less diverse and less specialized caterpillar assemblages. Our results suggest that a combination of phylogenetic information and compositional structure of the host plant community provides useful measures to predict the structure of herbivore assemblages among coexisting plant species.